Pengaruh Influencer Marketing, Live Streaming Dan Online Customer Review Terhadap Keputusan Pembelian Lozy Hijab Di Tiktok - Riska Bimbi; Sumiati (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Social media is currently used to carry out digital transactions by making purchases on e-commerce. The existence of influencers and live streaming features through the TikTok application is a new promotional method for sellers to share the advantages of their products, as well as interesting content that makes consumers interested in buying and is able to provide positive or negative communication related to the product that consumers share after using the product. bought it. This type of research uses quantitative research with Non- Probability Sampling with Purposive Sampling Technique. The population in this study was a sample of 100 respondents who used lozzy hijab products with multiple linear regression analysis analyzed using SPSS 26. The results of this research show that Influencer Marketing (X1) has a positive and significant effect on Purchasing Decisions (Y), Live Streaming (X2) has a positive and significant effect on Purchasing Decisions (Y), Online Customer Reviews (X3) has a positive and significant effect on Purchasing Decisions (Y), Influencer Marketing, Live Streaming, and Online Customer Reviews simultaneously have a positive and significant influence on Purchasing Decisions (Y).